2011
DOI: 10.1039/c0dt01660h
|View full text |Cite
|
Sign up to set email alerts
|

Rational creation of chiral multinuclear and metallosupramolecular compounds from thiol-containing amino acids

Abstract: Developments in the rational creation of chiral multinuclear and metallosupramolecular compounds based on linear-type metal complexes with penicillaminate (pen), as well as their functionality as a multidentate chiral metalloligand, is the main subject of this paper. The reactions of a mononuclear Au(I) complex, [Au(d-pen)(2)](3-), in which two d-pen ligands bind to an Au(I) center through thiolato S atoms, with transition metal ions afford a variety of S-bridged heterobimetallic multinuclear complexes, the st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
31
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
6
1

Relationship

6
1

Authors

Journals

citations
Cited by 71 publications
(31 citation statements)
references
References 160 publications
0
31
0
Order By: Relevance
“…It has been recognized that a variety of polynuclear and supramolecular coordination compounds are created from thiol-containing amino acids, such as l -cysteine ( l -H 2 cys), d -penicillamine ( d -H 2 pen), and their derivatives, in combination with 3d and 4d transition metal ions, because these amino acids can adopt various coordination modes to multiple metal centres by using amine, carboxyl, and/or thiol groups dependent on their protonation/deprotonation states 14 . We found that the introduction of hydrophobic dppe (1,2-bis(diphenylphosphino)ethane) into a gold(I)-cobalt(III) coordination system with hydrophilic d -pen affords a cationic Au I 4 Co III 2 hexanuclear complex, [Au 4 Co 2 (dppe) 2 ( d -pen) 4 ] 2+ ([ 1 ] 2+ ), in which two Co III centres are spanned by two [Au I 2 (dppe)( d -pen) 2 ] 2− linkers 13 .…”
Section: Introductionmentioning
confidence: 99%
“…It has been recognized that a variety of polynuclear and supramolecular coordination compounds are created from thiol-containing amino acids, such as l -cysteine ( l -H 2 cys), d -penicillamine ( d -H 2 pen), and their derivatives, in combination with 3d and 4d transition metal ions, because these amino acids can adopt various coordination modes to multiple metal centres by using amine, carboxyl, and/or thiol groups dependent on their protonation/deprotonation states 14 . We found that the introduction of hydrophobic dppe (1,2-bis(diphenylphosphino)ethane) into a gold(I)-cobalt(III) coordination system with hydrophilic d -pen affords a cationic Au I 4 Co III 2 hexanuclear complex, [Au 4 Co 2 (dppe) 2 ( d -pen) 4 ] 2+ ([ 1 ] 2+ ), in which two Co III centres are spanned by two [Au I 2 (dppe)( d -pen) 2 ] 2− linkers 13 .…”
Section: Introductionmentioning
confidence: 99%
“…We found that [H 2 1 ] coordinates to divalent transition‐metal ions (M = Ni II , Zn II ) in a chelating manner, forming an S‐bridged Au 2 M trinuclear structure with an 8‐membered MAu 2 S 2 P 2 C metalloring, [M{Au 2 (dppm)( d ‐pen) 2 }] ([ 20 ] for M = Ni II , [ 21 ] for M = Zn II ) (Scheme ) 16,17. This is in sharp contrast to the coordination mode of [Au( d ‐pen‐ S ) 2 ] 3– , which uniformly adopts a bridging‐type mode 10,11…”
Section: Coordination Behavior Of Diphosphine‐bridged Digold(i) Metalmentioning
confidence: 99%
“…The trinuclear complexes [ 20 ] and [ 21 ] contain an octahedral [M( d ‐pen) 2 ] 2– unit that is bound to a [Au 2 (dppm)] 2+ moiety through S atoms. The M atom selectively adopts a distorted N 2 O 2 S 2 octahedral geometry with a trans (O) geometric configuration 10. The two bridging S atoms are asymmetric and have the R chiral configuration.…”
Section: Coordination Behavior Of Diphosphine‐bridged Digold(i) Metalmentioning
confidence: 99%
See 2 more Smart Citations